Characteristics of the coenopopulation Platanthera bifolia (L.) Rich. in conditions of different nature management modes - Perestoronina Olga; Shabalkina Svetlana (BIO Web of Conferences)
The paper considers ecological-phytocoenotic, structural-populational characteristics of Platanthera bifolia (L.) Rich. in phytocoenoses in conditions of different nature management modes in the Kirov region. Two coenopopulations (CP 1, CP 2) in green moss pine forests and one coenopopulation (CP 3) in a spruce-birch poly-herb forest were considered. As a result of vegetation analysis with the use of D.N. Tsyganov phytoindication scales, it was found out that in the green moss pine forests the growth of Platanthera bifolia is being restricted by lack of light and soil moistening, while in the poly-herb forest the conditions are more optimal for the species. The coenopopulations under research are numerous; two periods and seven states are distinguished in the ontogenesis. The ontogenetic specter is normal, full-member (green moss pine forests) and not full-member (due to lack of plantlets) in a spruce-birch poly-herb forest. A high share of plants in the pregenerative period (90.6%) in CP 3 suggests successive reproduction in conditions of dynamic succession processes which took place after natural damage of the community. The coenopopulations considered are steady; they are capable of self-maintaining, still. The nature management modes analysis showed relative resistance of the species to natural factors and anthropogenic ipact.